Understanding The Essence Of E-Learning and Knowledge of Its Implementation on Academic Performance of Students. (International Journal of Food and Nutritional Sciences, 2022)
E-learning, which leverages electronic technologies for educational purposes, has seen a surge in popularity across the globe. As e-learning becomes more prevalent, evaluating its effectiveness and impact on academic performance has become crucial. Despite its growing use, many learners in India still do not fully grasp the concept. This paper aims to explore e-learning and assess its influence on students' academic achievements. Through the development and analysis of a questionnaire, this research indicates that e-learning holds promise for improving learning outcomes compared to traditional methods, and suggests a need for further advancements to transform education in India.